Expression of transformating growth factor beta 1 (TGF- β1) in the healing process of a mouse achilles tendon rupture (Rattus norvegicus) given platelet rich plasma - Ricky Aldofan; Zulkarnaini; Dasrul; Safrizal Rahman; T. Nanta Aulia; Jufriady Ismy (Journal of International Surgery and Clinical Medicine, 2021)
Introduction: Platelet rich plasma (PRP) contains not only several growth factors but also proinflammatory cytokines that promote the healing process of tendon ruptures. Therefore, this study aimed to determine the effect of PRP administration on TGF- β1 expression during the healing process of Achilles tendon rupture in white rats (Rattus norvegicus). Method: This study was an experimental research with a Posttest-Only Control Group Design approach. This study enrolled 30 male white rats with a ruptured Achilles tendon, aged 3-4 months and weighing 200-250 grams.  The rats were randomly divided into 2 groups. The first (I) group as the control group included rats with Achilles tendon rupture without PRP administration, and group II as the experimental group included rats with Achilles tendon rupture with PRP 100 ul administration. Equal number of white rats from both groups were observed in 3 different times (on the day 7th, 14th, and 21st) after intervention. Part of the substance of the right Achilles tendon of each white rat was taken for examination of TGF-β1 expression by immunohistochemical examination with anti-TGF- β1 primary antibody. The data were analyzed by using SPSS 25.0. The descriptive data were provided in table, and the analytic data were analyzed by using unpaired t-test. The significant p value was <0.05. Results: We established that the intensity of TGF- β1 expression of Achilles tendon in the experimental group (with PRP administration) was statistically significant (P<0.05) compared to the control group. TGF- β1 expression in the experimental group established stronger and more extensive staining at weeks 1 and 2 (P < 0.05), while the control group established more extensive staining at week 3 (P < 0,05). Conclusion: PRP administration can increase TGF-β1 expression during the healing process of Achilles tendon rupture in white rats (Rattus norvegicus) and its statistically significant.